Testing the initial 230Th/232Th for "Known Age Carbonate" and its significance for 230Th dating and paleoclimate research. (10th January 2022) - Li, Ting-Yong; Wang, Xuefeng; Chen, Chao-Jun; Tan, Ming; Wu, Yao
Abstract: The 230 Th dating ( 238 U– 234 U– 230 Th dating method) has become one of the most important dating methods for Quaternary research. However, the 230 Th/ 232 Th ratio of 4.4 ± 2.2ⅹ10 −6 is widely used for age correction in 230 Th dating method. Here, we collected active speleothems with exactly known age and zero-year-old calcium carbonate from caves and dated them by 230 Th dating. Our data indicated that the initial 230 Th/ 232 Th ratio can be one order of magnitude higher than the ratio of 4.4 ± 2.2 × 10 −6 . High initial 230 Th/ 232 Th ratio may result in false and comparatively old calculated age than the real age of young samples with low 238 U concentration. So, the accurate initial 230 Th/ 232 Th ratio of active speleothem deposited in the same cave, instead of the general initial 230 Th/ 232 Th ratio, is essential for the precise age correction of young speleothem samples of low 238 U concentration. Finally, we proposed a procedure to correlate modern observation and speleothem based paleoclimate reconstruction, on the basis of precise 230 Th age which corrected by the true initial 230 Th/ 232 Th ratio.